Host range and symptomatology of a graft-transmissible pathogen causing bud union crease of citrus on trifoliate rootstocks - Galipienso, Luis; Navarro, Luis; Ballester-Olmos, José F.; Pina, José A.; Moreno, Pedro; Guerri, José (2017)
A graft-transmissible pathogen causing bud union crease of Nagami kumquat SRA-153 on Troyer citrange was characterized for host range and symptomatology. Buds of Marsh grapefruit, Nules clementine, Eureka lemon and Pineapple sweet orange preinoculated with kumquat SRA-153 were propagated on citrange rootstocks. Some plants of Nules clementine and Eureka lemon had developed bud union crease six months after propagation, whereas all Marsh grapefruit and Pineapple sweet orange plants still showed normal bud union after one year. On indexing these preinoculated species, Nules clementine and Eureka lemon caused vein clearing in Pineapple sweet orange and Dweet tangor, chlorotic blotching in Dweet tangor and stem pitting in Etrog citron, whereas Marsh grapefruit and Pineapple sweet orange caused only chlorotic blotching in Dweet tangor and stem pitting in Etrog citron. Following shoot-tip grafting in vitro of kumquat SRA-153, kumquats 38-1 and 497-2 obtained from it caused chlorotic blotching in Dweet tangor and stem pitting in Etrog citron, but not vein clearing in Pineapple sweet orange and Dweet tangor or bud union crease when propagated on citrange. These results suggest the presence of at least two pathogens or pathogen strains in kumquat SRA-153 and the elimination of one of them after shoot-tip grafting in vitro or inoculation on Marsh grapefruit or Pineapple sweet orange. They also indicate that the pathogens in kumquat SRA-153 can be detected by indexing on Dweet tangor or Etrog citron.